Penerapan Teknologi Informasi di Lingkungan Mahkamah Agung Republik Indonesia dalam Rangka Memperlancar Penanganan Berkas Perkara - Sari, Anita; Kartika, Tantri; Karli, Karli (Postulat, 2024)
A case settlement between the party who is the victim and the party who is the perpetrator is known as case dispute resolution. The process of resolving a case can take one of two forms: through litigation (in the court) or non-litigation (outside of court). Using methods from a literature review, the purpose of this study is to examine how digital justice is affected by technology and innovation in law enforcement. The application of information technology to increase the effectiveness and efficiency of time in handling case files, particularly at the Supreme Court of the Republic of Indonesia, has changed the way law enforcement operates in the ever-growing digital era. These technological developments include big data analysis, artificial intelligence, and digital forensic technology. Indonesia. This study's problem formulation is as follows: 1) How are cases resolved in court? 2) How are efforts to speed up the resolution of cases in court according to PERMA Number 4 of 2020 concerning Electronic Administration and Trial of Criminal Cases in Court? Legal behavioral products, such as reviewing laws, are used in normative case studies in normative legal research methods (normative law study). The issuance of PERMA Number 4 in 2020 will accelerate the resolution of cases in court through administrative procedures and electronic broadcasting. This could increase the effectiveness and efficiency of broadcasting principles and reduce the broadcasting of cases in court, particularly given the existence of PERMA Number 1 in 2019.